Stem Cell Research & Therapy - O'Brien, Timothy; Tuan, Rocky S.; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
Stem Cell Research & Therapy is the major forum for translational research into stem cell therapies. An international peer-reviewed journal, it publishes high-quality open access research articles with a special emphasis on basic, translational and clinical research into stem cell therapeutics and regenerative therapies, including animal models and clinical trials. The journal also provides reviews, commentaries, reports and methods. Please note that we do not accept pre-clinical systematic reviews, case reports, or meta-analyses. Topics covered include, but are not limited to: Adult stem cells Animal models Biophysics and mechanobiology Cancer stem cells Cell culture and manufacture Clinical studies Disease modeling and drug screening Embryonic stem cells Ethical, legal and social aspects Genetics and epigenetics Genomics/proteomics/metabolomics Germ cells Immunology Induced pluripotent stem cells Regenerative medicine Stem cell differentiation, proliferation and migration Stem cell therapy/transplantation Technologies Tissue engineering and biomaterials.
Keywords: Stem cells; Cytology; Regenerative medicine; Biomedical engineering; Stem Cell Biology; Cell Biology; Regenerative Medicine and Tissue Engineering; Biomedical Engineering and Bioengineering